2014
DOI: 10.1631/jzus.b1300133
|View full text |Cite
|
Sign up to set email alerts
|

Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population

Abstract: Abstract:Objective: A study in a Caucasian population has identified two single-nucleotide polymorphisms (SNPs) in ZNF533, one in DOCK4, and two in IMMP2L, which were all significantly associated with autism. They are located in AUTS1 and AUTS5, which have been identified as autism susceptibility loci in several genome-wide screens. The present study aimed to investigate whether ZNF533, DOCK4, and IMMP2L genes are also associated with autism in a northeastern Chinese Han population. Methods: We performed a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…DOCK4 is located at chromosome band 7q31.1 [18,19], an autism-susceptible locus resided by several ASD-associated genes involved in development and language regulation. Recent studies have identified a number of DOCK4 variations associated with ASD, including both single nucleotide variations (SNVs) and chromosome microdeletions or duplications (Supplementary Table 1) [18][19][20][21][22][23][24][25][26]. Many of these variations are believed to result in loss-of-function of DOCK4.…”
Section: Introductionmentioning
confidence: 99%
“…DOCK4 is located at chromosome band 7q31.1 [18,19], an autism-susceptible locus resided by several ASD-associated genes involved in development and language regulation. Recent studies have identified a number of DOCK4 variations associated with ASD, including both single nucleotide variations (SNVs) and chromosome microdeletions or duplications (Supplementary Table 1) [18][19][20][21][22][23][24][25][26]. Many of these variations are believed to result in loss-of-function of DOCK4.…”
Section: Introductionmentioning
confidence: 99%
“…Several data indicate that mutations/deletions of the IMMP2L gene are associated with ASD; however, the existence of such an association is still debated [Petek et al, 2007;Liang et al, 2014]. The notion that IMMP2L alter- ations may predispose to cognitive/behavioral disturbances is supported also by in vivo models: for example, in mice heterozygous for an inactive Immp2l gene, increase of ischemic brain damage and apoptosis of cerebellar neurons have been detected [Ma et al, 2017;Liu et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Several data indicate that alterations of the IMMP2L gene are linked with autism spectrum disorders (ASD) [Petek et al, 2001;Muhle et al, 2004;Maestrini et al, 2010;Casey et al, 2012]. However, this is discussed controversially, since some studies do not support this association [Petek et al, 2007;Liang et al, 2014]. For example, Zhang et al [2018], by performing a trio family study and meta-analysis, found no evidence for an association between IMMP2L gene deletions and ASD.…”
mentioning
confidence: 99%
“…The complexity arises when we observed independent studies with negative association. Petek et al () and Liang et al () found no evidence of association in their ASD cohort of 95 multiples ASD families and 370 ASD trios in Chinese Han population, respectively.…”
Section: Introductionmentioning
confidence: 92%